HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN MOTIVASI SEMBUH PASIEN RAWAT INAP - Mery Sambo (Jurnal Keperawatan Florence Nightingale, 2018)
Motivation to recover from an illness is needed by someone in life. Therapeutic communication skills of nurses can support and encourage as well as the information becomes a positive outlet for patients to receive state is experienced and able to make changes that can improve the health of patients. The purpose of this research is to determine the relationship of therapeutic communication nurse with motivation to recover inpatients. This study design is an Analytic observational cross sectional. The technique uses purposive sampling with a sample of 52 people. Data analysis uses statistical techniques of data collection using the questionnaire. The result of this research result indicates that the communication of nurses in both categories as many as 46 people (88.5%), patients who have a high motivation to recover as many as 44 people (84.6%). The statistical results showed no association with the motivation of therapeutic communication cured of inpatients with a value of p = 0.002 (p <0.05). This research can be concluded that there is relationship therapeutic communication of nurses with the inpatient’s motive to recover.